Structure, bonding, and catecholase mechanism of copper bispidine complexes - Comba, Peter; Martin, Bodo; Muruganantham, Amsaveni; Straub, Johannes (Inorganic chemistry, 2012)
Oxygen activation by copper(I) complexes with tetra- or pentadentate mono- or dinucleating bispidine ligands is known to lead to unusually stable end-on-[{(bispidine)Cu}2(O2)]2+ complexes (bispidines are methyl-2,4-bis(2-pyridin-yl)-3,7-diazabicyclo-[3.3.1]-nonane-9-diol-1,5-dicarboxylates); catecholase activity of these dinuclear CuII/I systems has been demonstrated experimentally, and the mechanism has been thoroughly analyzed. The present density functional theory (DFT) based study provides an analysis of the electronic structure and catalytic activity of [{(bispidine)Cu}2(O2)]2+. As a result of the unique square pyramidal coordination geometry, the dx2-y2 ground state leads to an unusual σ/π bonding pattern, responsible for the stability of the peroxo complex and the observed catecholase activity with a unique mechanistic pathway. The oxidation of catechol to ortho-quinone (one molecule per catalytic cycle and concomitant formation of one equivalent of H2O2) is shown to occur via an associative, stepwise pathway. The unusual stability of the end-on-peroxo-dicopper(II) complex and isomerization to copper(II) complexes with chelating catecholate ligands, which inhibit the catalytic cycle, are shown to be responsible for an only moderate catalytic activity.